2017
DOI: 10.5194/acp-2017-761
|View full text |Cite
|
Sign up to set email alerts
|

Considering the future of anthropogenic gas-phase organic compound emissions and the increasing influence of non-combustion sources on urban air quality

Abstract: 12Decades of policy in developed regions has successfully reduced total anthropogenic emissions of 13 gas-phase organic compounds, especially volatile organic compounds (VOCs), with an intentional, 14 sustained focus on motor vehicles and other combustion-related sources. We examine potential 15 secondary organic aerosol (SOA) and ozone formation in our case study megacity (Los Angeles), 16 and demonstrate that non-combustion-related sources now contribute a major fraction of SOA and 17 ozone precursors. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…To evaluate the importance of asphalt-related emissions on urban scales, we assessed their relative contributions of SOA precursors including a focus on I/SVOCs given their established role in SOA production (4). We compared their emissions to known sources in the more developed California-based emission inventories and studies, especially the South Coast Air Basin (SoCAB), which is an important historical urban air quality case study (1,2). Road asphalt is responsible for 86 to 87% of total liquid asphalt binder used in California and the United States ( fig.…”
Section: Comparing Intermediate-and Semivolatile Emissions and Soa Prmentioning
confidence: 99%
See 3 more Smart Citations
“…To evaluate the importance of asphalt-related emissions on urban scales, we assessed their relative contributions of SOA precursors including a focus on I/SVOCs given their established role in SOA production (4). We compared their emissions to known sources in the more developed California-based emission inventories and studies, especially the South Coast Air Basin (SoCAB), which is an important historical urban air quality case study (1,2). Road asphalt is responsible for 86 to 87% of total liquid asphalt binder used in California and the United States ( fig.…”
Section: Comparing Intermediate-and Semivolatile Emissions and Soa Prmentioning
confidence: 99%
“…They can be classified into three pathways: (i) solvent evaporation, (ii) volatilization of solutes, and (iii) off-gassing of compounds not present in product formulations (e.g., degradation by-products) as is the case with asphalt-related emissions (1). Emission time scales from any applied products and materials are highly dependent on temperature, film thickness, and compound volatility and can extend to months or longer for I/SVOCs (1). Model results estimate that 70 to 86% of urban SOA in metropolitan Los Angeles comes from the oxidation of primary I/SVOC emissions (4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that emissions from volatile chemical products (VCPs), defined as pesticides, coatings, inks, adhesives, personal care products, and cleaning agents (McDonald et al, 2018) , as well as cooking emissions (Hayes et al, 2015) , are important. While total amounts of ASOA precursors released in cities have dramatically declined (largely due to three-way catalytic converters in cars (Warneke et al, 2012;Pollack et al, 2013;Zhao et al, 2017;Khare and Gentner, 2018) ), VCPs have not declined as quickly (Khare and Gentner, 2018;McDonald et al, 2018) . Besides a few cities in the US (Coggon et al, 2018;Khare and Gentner, 2018;McDonald et al, 2018) , extensive VCP emission quantification has not yet been published.…”
Section: Introductionmentioning
confidence: 99%